Pengaruh Penambahan Blondo Terhadap Karakteristik Flakes Tepung Beras Merah - Aulia Adha, Ridha; Wisaniyasa, Ni Wayan; Yusa, Ni Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 4 (2021): Jurnal ITEPADO - 10.24843/itepa.2021.v10.i04.p17, 2021)
This study aims to determine the effect of addition of blondo on the characteristics of brown rice flakes and determine the appropriate addition of blondo to get the best brown rice flakes characteristics. The design used in this study was Completely Randomized Design with the treatment of adding blondo consisting of 6 levels, namely 0%, 30%, 40%, 50%, 60% and 70%. This study was repeated three times to obtain 18 experimental units. The data obtained were analyzed by analysis of variance and if the treatment had a significant effect it was followed by DMRT (Duncan Multiple Range Test). The results showed that the addition of blondo had a significant effect on water content, protein content, fat content, carbohydrate content, crude fiber content, water absorption, aroma scoring test, taste scoring test and texture scoring test. Brown rice flakes with the addition of 40% blondo was the best treatment with characteristics water content 3.58%, ash content 1.62%, protein content 10.97%, fat content 13.76%, carbohydrate content 70.07%, crude fiber content 4.21%, water absorption 43.25%, and color rather liked, aroma rather typical coconut and rather liked, taste rather typical coconut and rather liked, texture crispy and rather liked and overall acceptance rather liked.